Exploring the Molecular Machinery of Denitrification in Haloferax mediterranei Through Proteomics - Torregrosa-Crespo, Javier; Pire, Carmen; Richardson, David J.; Martínez-Espinosa, Rosa María (Frontiers in Microbiology, 2020)
Many proteins and enzymes involved in denitrification in haloarchaea can be inferred to be located between the cytoplasmic membrane and the S-layer, based on the presence of a Tat signal sequence and the orientation of the active site that some of these enzymes have. The membrane fraction of the haloarchaeon Haloferax mediterranei (R-4), grown under anaerobic conditions in the presence of nitrate, was solubilised to identify the respiratory proteins associated or anchored to it. Using Triton X-100, CHAPS and n-Octyl-β-d-glucopyranoside at different concentrations we found the best conditions for isolating membrane proteins in micelles, in which enzymatic activity and stability were maintained. Then, they were subjected to purification using two chromatographic steps followed by the analysis of the eluents by NANO-ESI Chip-HPLC-MS/MS. The results showed that the four main enzymes of denitrification (nitrate, nitrite, nitric oxide and nitrous oxide reductases) in H. mediterranei were identified and they were co-purified thanks to the micelles made with Triton X-100 (20% w/v for membrane solubilisation and 0.2% w/v in the buffers used during purification). In addition, several accessory proteins involved in electron transfer processes during anaerobic respiration as well as proteins supporting ATP synthesis, redox balancing and oxygen sensing were detected. This is the first characterization of anaerobic membrane proteome of haloarchaea under denitrifying conditions using liquid chromatography-mass spectrometry. It provides new information for a better understanding of the anaerobic respiration in haloarchaea.